STUDY OF POPULATION AND HOME RANGE OF THOMAS LAGUR (Presbytis thomasi) AT SORAYA RESEARCH STATION, LEUSER ECOSYSTEM - Syaukani Syaukani (Universitas Syiah Kuala, 2012)
A primate Presbytis thomasi lives in a group with uni-male systems (only one adult make in agroup) at Soraya Research Station. These primates performer their daily activity in one home-range and also protect their home-range with provides a specific vocal (loud-call). There were six groups of Langur with 6-12 individual of each group. The width of home-range shows a variation in each group. The overlapping of home-range ofte causes probles among males and the looser will have to leave as weel as losing all parts of the groups.